COLLABORATIVE GOVERNANCE DALAM PERKEMBANGAN PARIWISATA DI KAWASAN SENGGIGI KABUPATEN LOMBOK BARAT - Ahmad Fitra Baiti Rahman; Amil; Ilham Zitri (Nusantara Hasana Journal, 2023)
This research was conducted with the aim of knowing collaborative governance in the development of tourism in the Senggigi area of West Lombok regency. The development of a tourist spot with optimal resource management can be shown through the synergy that is built between various stakeholders, both government, private and community. In addition, as a material consideration in making tourism potential development decisions, it is important to know how the collaboration that has been built and what factors encourage and inhibit collaboration in developing a tourism object. The method that researchers use is a descriptive qualitative method. This method was chosen because it is suitable for accurately describing individual characteristics, symptoms, circumstances and situations of certain groups. This study uses data collection methods through various forms such as observation, interviews, and documentation. This study uses collaborative governance theory from DeSave which provides 7 (seven) indicators as analytical tools. The research results show that collaborative governance in tourism development in the Senggigi area as a whole has not shown maximum results. This can be seen from: a weak network structure, marked by the absence of related actors. Commitment to goals (not good), seen from the absence of common goals and common missions created. Level of trust (weak), where strong trust is only built between collaborative actors between government agencies. Access to power (good enough), where the Tourism Office is very open and knows the performance of other collaborating actors. Division of accountability (good enough), where each collaborative actor has their own duties. Information sharing (not optimal), where the information is mostly shared only with those who are members of government agencies. Access to resources (not yet maximized), this is evidenced by infrastructure development that is still inadequate, even though the development of quality human resources can be said to be already under way.